New venture creation: How start-ups grow? (2017)
Start-ups, often seen as sources of innovation and change, are prone to failure and accordingly they are attracting considerable attention not least from policy makers and Government officials. However, the various new venture creation studies that have emerged since the early 1980s lack cohesiveness, and the domain remains controversial. This article not only exposes the limitations of the existing body of understanding on the topic  but  attempts to develop a more  comprehensive and comprehendible  framework for start up (new venture) creation. To do so it uses the frameworks proposed by Whetten, and March and Smith to develop 11 propositions. The resultant model suggests that the creation of a start up involves the identification of an idea or opportunity by an entrepreneur who subsequently organizes a series of activities, mobilizes resources and creates competence using his/her networks in an environment in order to create value. It sheds light on the start-up (new venture) creation process and has relevance for entrepreneurs, policy makers and researchers.